Mainstreaming Gender in Kar?ch?’s Public Transport Policy - Panjwani, Neha (European Journal of Sustainable Development, 2018)
Conversations around gender inequality often focus on access to health, education, and workplace rights, but scarcely concern the transportation sector. The latter is highly gender discriminatory, especially in developing countries such as Pakistan, affecting the mobility of women and third genders, who face inequities in the provision and accessibility of this public service. Such constraints to safe, efficient, and comfortable mobility create serious problems for certain genders reflecting their economic security: this by extension is both a cause and an effect of social inequality, and the failure of federal budget allocation towards transportation leading to profound gender disparities in cities. It not only affects mobility but also, consequently, shapes the way in which space is occupied by women in public spheres. In the light of these challenges, this policy paper seeks to highlight the specific mobility challenges faced by women and transgender population, in the metropolis of Kar?ch?, who commute via public transport that includes buses, taxis and rickshaws. It highlights existing shortcomings in, and recommends an urgent focus on a more inclusive, need-based public transportation system. By drawing on the principles of gender mainstreaming interventions in public transportation in other countries, and data from first-hand interviews with local conductors, bus drivers and passengers – this policy makes some pragmatic recommendations, paying special attention to issues of inclusion, accessibility, safety and mobility. The implications of this study are to enhance evidence-based policy-making in transportation with particular focus on urban planning and gender – sensitive city development.